Cases on technologies for teaching criminology and victimology methodologies and practices - Sette, Raffaella; IGI eBooks; IGI Global (Hershey, Pa. : Information Science Reference : IGI Global (701 E. Chocolate Ave., Hershey, PA, 17033, USA), 2010)
As the explanation of crime and the social reaction to it depends on historical and cultural contexts, didactic methodologies are subject to continuous change in relation to theories and needs strictly linked to the profession. With examinations into real-life situations, this unique publication analyzes the benefits and disadvantages of various teaching methodologies in universities, police academies, and crime victim services.
Section 3. Criminology and Victimology: Disciplines that Look at the Professionals (of Teaching): Chapter 12. The Present Cybercrime: Operational and Instructive Experiences / Antonio Apruzzese -- Chapter 13. The Professional Training of the Italian Surveillance Magistracy: The Useful Knowledge of Criminology and Victimology for a Working Italian Prison System / Giovanna Fanci -- Chapter 14. Teaching Criminology to Police Officers: Bologna's Local Police Case / Andrea Piselli -- Chapter 15. University Branches in Prison: The Italian Case / Daniela Ronco.
Includes bibliographical references (p. 259) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 12, 2010).
Keywords: Criminology -- Study and teaching; Victims of crime; Criminology -- Case studies; Victims of crime -- Case studies; Electronic books